Continuous EEG Monitoring in Critically Ill Patients with CNS Infections - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The prevalence, predictors, and clinical significance of electrographic seizures (ESz) or periodic epileptiform discharges (PEDs) recorded during continuous electroencephalographic monitoring in critically ill patients with CNS infections were evaluated in a study at Columbia University Medical Center, New York, NY.